Do orthotic walkers affect knee and hip function during gait?. (February 2016) - Richards, Jim; Payne, Katherine; Myatt, Darren; Chohan, Ambreen
Background and Aim: Much previous research on orthotic walkers has focussed on their ability to offload structures in the foot and ankle; however, little is known about their effects on lower limb mechanics. This study aimed to determine effects of two orthotic walkers on the biomechanics of the knee and hip joints compared to standardised footwear. Technique: A total of 10 healthy participants walked under three conditions: Walker A (Össur, Iceland), Walker B (DJO Global, USA) and standardised footwear (Hotter, UK). Kinematic and kinetic data were collected using a Qualisys motion analysis system (Qualisys Medical AB, Sweden) and force plates (AMTI, Boston, MA, USA). Significant differences were seen in hip kinematics and knee moments between walkers and standardised footwear and in knee kinematics between Walker A and standardised footwear. Discussion: Both walkers show significant kinematic and kinetic differences compared with standardised footwear; however, Walker A appeared to produce greater deviation, including potentially damaging greater hyperextension moments at the knee. Clinical relevance: Further research is needed into the effects of orthotic walkers on knee and hip joint mechanics, which should help to inform future designs of walker, with greater focus on obtaining a more normal gait pattern.